1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Expression of the Gene Encoding Secretor‐Type Galactoside 2‐α‐l‐fucosyltransferase (FUT2)

Abstract: The expression and secretion of ABO antigens in epithelial cells of glands are controlled by secretortype a(l,2)fucosyltransferase activity. We have examined the expression of the secretor-type a( 1,2)fucosyltransferase gene (FUT2) and a pseudogene of FUT2 (Secl) in several tumor cell lines by northern blot and/or reverse-transcription-PCR (RT-PCR) analyses. Transcripts of FUT2 were found in total RNA from ovarian, gastric and colonic cancer cell lines but not from six leukemic cell lines, including erythroleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…(CA11) is not yet known, the final intron is labeled N and the final exon Nϩ1. Seventy-five basepairs of the CA11 antisense strand are identical to the first 75 bp of the ovarian cancer cell Sec1 transcripts (Koda et al, 1997) from the FUT2P gene. FUT2P is a pseudogene, not expressed in normal tissues examined by Koda et al (1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(CA11) is not yet known, the final intron is labeled N and the final exon Nϩ1. Seventy-five basepairs of the CA11 antisense strand are identical to the first 75 bp of the ovarian cancer cell Sec1 transcripts (Koda et al, 1997) from the FUT2P gene. FUT2P is a pseudogene, not expressed in normal tissues examined by Koda et al (1997).…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-five basepairs of the CA11 antisense strand are identical to the first 75 bp of the ovarian cancer cell Sec1 transcripts (Koda et al, 1997) from the FUT2P gene. FUT2P is a pseudogene, not expressed in normal tissues examined by Koda et al (1997). It is homologous to, and part of, a cluster containing the FUT2 and FUT1 genes, which encode the Secretor and H blood groups, respectively (Kelly et al, 1995; GenBank U17895; OMIM 182100).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have determined the gene structure of FUT2 (Koda et al 1997a). The results indicate that FUT2 consists of two exons that are separated by a 7-kb intron sequence.…”
Section: Introductionmentioning
confidence: 96%
“…Secretors, who have ABO antigens in saliva, have at least one functional Se allele, and nonsecretors, who fail to express ABO antigens in saliva, are homozygous for the nonfunctional se allele. After the isolation of cDNA and genomic DNA of the FUT2 gene (Kelly et al 1995;Koda et al 1997a), molecular analysis of FUT2 has indicated that null alleles with a single base substitution in the protein coding region of FUT2 (G428A, A385T, C571T, C628T and G849A) were responsible for the inactivation of Se enzyme (Kelly et al 1995;Yu et al 1996;Koda et al 1996). The findings from these studies suggested that these null alleles were geographic-specific and perhaps therefore race-specific.…”
Section: Introductionmentioning
confidence: 99%